2022
DOI: 10.1177/10406387221102123
|View full text |Cite
|
Sign up to set email alerts
|

Enzootic bovine leukosis in a 21-month-old Japanese Black cow with high susceptibility

Abstract: A 21-mo-old Japanese Black beef cow had swollen mandibular and superficial cervical lymph nodes. Fine-needle aspiration cytology of the superficial cervical lymph node revealed large lymphoblasts with mitoses present. The bovine leukemia virus (BLV) proviral load was relatively high, and phylogenetic analysis of the whole BLV genome classified the BLV strain as one with high viral replication activity. Genotyping of bovine leukocyte antigen genes indicated that the cow was susceptible to enzootic bovine leukos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although almost all BLV-infected animals remain clinically asymptomatic throughout their lifespan, less than 5% of the infected cattle develop EBL [ 2 ]. Due to the lengthy latency period required by BLV, EBL is commonly seen in cattle older than 3 years [ 3 ], while onset of EBL in cattle under 3 years old has also been observed in Japan [ 4 6 ]. Although some factors related to onset of EBL in young cattle have been reported [ 6 8 ], the mechanism of early EBL onset is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although almost all BLV-infected animals remain clinically asymptomatic throughout their lifespan, less than 5% of the infected cattle develop EBL [ 2 ]. Due to the lengthy latency period required by BLV, EBL is commonly seen in cattle older than 3 years [ 3 ], while onset of EBL in cattle under 3 years old has also been observed in Japan [ 4 6 ]. Although some factors related to onset of EBL in young cattle have been reported [ 6 8 ], the mechanism of early EBL onset is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Because proviral and disease progression were positively correlated, the pathogenicity might be different among groups. In addition, a case of EBL caused by BLV classified as group A in young cattle has been reported [ 6 ]. However, the relationship between early onset of EBL and BLV groups has been unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzootic bovine leukosis (EBL) is a B-cell lymphoma caused by bovine leukemia virus (BLV) in cattle older than 3 years of age [ 1 ], although early-onset EBL in cattle under 3 years of age has also been reported [ 7 , 12 ]. Enlargement of superficial lymph nodes and masses in the pelvic cavity are important clinical findings that can lead to a suspicion of EBL [ 1 , 2 ].…”
mentioning
confidence: 99%
“…BLV in EBL cattle under 3 years of age is mainly classified as Group A or B-1 [ 5 , 11 ], and previous studies have reported no Group C strain in EBL cattle. In fact, Group C BLV has only been isolated from cattle without EBL [ 5 , 7 , 11 ]. Here we report a clinical case of EBL caused by BLV classified as Group C in a 23-month-old Holstein-Friesian heifer with no enlargement of lymph nodes or masses in the pelvic cavity.…”
mentioning
confidence: 99%